TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE ON THE USE OF DIGITAL TECHNOLOGY IN TEACHING PRACTICE: A COMPARATIVE MODEL IN THE CONTEXT OF INDONESIAN AND MALAYSIA TEACHER PROSPECTIVE STUDENTS - Asih Jamila; Akhmad Habibi; Sofyan Sofyan; Mohd Faiz Mohd Yaakob (International Conference on Social and Islamic Studies, 2021)
This study examined Indonesian and Malaysian pre-service teachers’ digitaltechnology integration during teaching practices. Technological pedagogical andcontent knowledge (TPACK) framework was utilised to predict the use of digitaltechnology. The objectives of the study is to determine if the TPACK is a valid andreliable model to explain pre-service teachers’ digital technology integration duringteaching practices. Three hundred and seventy-seven pre-service teachers from twouniversities completed a 37-item survey instruments based on the TPACK and digitaltechnology implementation. The establishment of the instruments was conductedthrough content validity, face validity, and content validity index (CVI). Pilot studydata were analysed through the test of reliability and exploratory factor analysis(EFA). The current study results, computed through partial least squares structuralequation modelling (PLS-SEM) informed 13 hypotheses. Overall, the TPACKcomponents are interconnected and reported to be a valid model to help explainIndonesian and Malaysian pre-service teachers’ digital UICT during teachingpractice. Policy recommendations and suggestions are offered for the betterment ofIndoensian teachers’ level of TPACK and digital technology integration.